If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 3) + -1 = 35 Reorder the terms: 3(3 + 3x) + -1 = 35 (3 * 3 + 3x * 3) + -1 = 35 (9 + 9x) + -1 = 35 Reorder the terms: 9 + -1 + 9x = 35 Combine like terms: 9 + -1 = 8 8 + 9x = 35 Solving 8 + 9x = 35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 9x = 35 + -8 Combine like terms: 8 + -8 = 0 0 + 9x = 35 + -8 9x = 35 + -8 Combine like terms: 35 + -8 = 27 9x = 27 Divide each side by '9'. x = 3 Simplifying x = 3
| X+0.8x=27 | | (2x-18)+(4x)=180 | | 36=3(3+3x) | | 40x^2-47x+12=0 | | 3-2n-n=6 | | 3p+18=9p | | 2(t+4)-2(2t+3)=-4 | | -2k-3k=5 | | (z^2/6)-(z/2)-84=0 | | T=-16t^2+96t+1 | | 1+3x+x=1 | | 2=1-2m+3m | | 3=-1 | | R(p)=-4p^2+24000p | | 1=n+1+2n | | 2a+3a=-5 | | 75+(4x-9)=180 | | 5(0)=0 | | 3=x-3+2x | | 4+(3+8)=(4+3)+8 | | 1=-3x-3+1 | | H=-16t^2+12t+1700 | | (x-2)/(x^2-x-20) | | (-2/3)*(-4/15)*(45/16) | | 2=1-2m-3m | | n-1-3=-7 | | -2=-3n+n | | (3j+k)+(-4j-7k)-(j+k)= | | -8=-2+3k-3 | | -[3h+5y]-[7y+h]= | | 3u-3=-18 | | 180=(x+2)(5x+35) |